The Mediating Role of Product Innovation in The Influence of Market Orientation on The Performance of Silver Craft MSMEs in Sukawati District - Nyoman Tri Arta Wibawa Putra; Gede Bayu Rahanatha (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
This study aims to examine the influence of market orientation on the performance of micro, small, and medium-sized enterprises (MSMEs) with product innovation as a mediating variable, focusing on silver craft MSMEs in Sukawati District. The study was conducted on 102 silver craft MSMEs operating in the region. The sample was selected using simple random sampling, resulting in 82 respondents. Data analysis techniques employed in this study include descriptive statistics and inferential statistics through path analysis, classical assumption tests, the Sobel test, and the Variance Accounted For (VAF) test. The results indicate that market orientation has a positive and significant effect on MSME performance, market orientation positively and significantly influences product innovation, product innovation positively and significantly affects MSME performance, and product innovation mediates the effect of market orientation on MSME performance.